No One Is Prophet in His Own Land? Hezbollah and the Transnational Constitution of Non-State Armed Organizations - Olsson, Christian (PARTECIPAZIONE E CONFLITTO, 2022)
This paper deals with the transnational relations of non-state armed organizations. The question is why the organizationally more successful armed groups tend to revolve around transnational networks. The hypothesis is that it has to do with the way in which they generate cohesion within their combat units. Armed groups, especially clandestine ones, tend to co-opt parochial micro-solidarity networks for the purpose of maximizing small-unit military cohesion. At the level of the wider organization, however, this entails a significant risk: societal micro-cleavages between local networks tend to create rifts within the wider organization. This is especially the case for groups that initially have no access to centralized bureaucracies able to arbitrate local struggles through anonymous rule. The paper argues that their leaders can in this context harness transnational relations to distance themselves (physically and symbolically) from these struggles, thus allowing them to arbitrate these struggles from a position of "neutrality". The article focuses on Lebanese Hezbollah and its transnational clerical networks. In developing the argument, it highlights that the religious nature of these clerical networks was only indirectly a source of organizational cohesion. What matters is that their long-distance character allowed weaving together previously opposed shortrange networks.